A consensual qualitative research analysis of the experience of inmate hospice caregivers: Posttraumatic growth while incarcerated. Issue 4 (21st April 2017) - Depner, Rachel M.; Grant, Pei C.; Byrwa, David J.; Breier, Jennifer M.; Lodi-Smith, Jennifer; Kerr, Christopher W.; Luczkiewicz, Debra L.
ABSTRACT: A growing number of correctional facilities train inmates to provide end-of-life care for dying inmates. This study explores the phenomenological perspective of inmate-caregivers participating in an inmate-facilitated hospice program (IFHP) with regard to meaning and purpose in life, attitudes on death and dying, and perceived personal impact of participation. Twenty-two inmate-caregivers were interviewed at a maximum-security state correctional facility in the United States. The interviews were transcribed verbatim and analyzed using the Consensual Qualitative Research Methodology. Results suggest that participating in an IFHP may facilitate personal growth and transformation that mirrors the tenets of posttraumatic growth.